Efecto del almidón de papa y tiempo de cutterizado sobre las características físicas-químicas y organolépticas en una salchicha de calamar - Vivas Vélez, Ángel Rafael (2017)
Nowadays, the use of new raw materials such as sea products in meat products are the researching subject and evaluation based on conventional technologies to establish their quality and acceptance. The main objective in this researching was the evaluation for potato effect starch and cutter time on the physical-chemical and organoleptic characteristics of a squid sausage. Different potato doses of starch (4, 5 and 6%) and cutter time (4 and 6 min) were studied, it gave as a result: six treatments: T1 (4%: 4min), T2 (5%: 4min), T3 (6%: 4min), T4 (4%: 6min), T5 (5%: 6min), T6 (6%: 6min). A completely randomized design (DCA) was used in bifactorial arrangement A * B with 3 replicates for each treatment, obtaining 18 experimental units of 4kg each. They were evaluated as physical-chemical parameters; pH, Bake Loss, hardness, elasticity, firmness, chewability, and as Sensory Attributes: Color, Odor, Flavor, Consistency and Appearance, with trained tasters from Piggis S.A. The data analysis was done in the statistical program Spss version 21. The best treatment resulted in the T6 that contained a longer cutter time (6 min) and a higher percentage of potato starch (6%). All treatments were complied with the requirements of NORMA INEN 1338 2012 for meat products with the exception of the pH variable that did not comply with INEN 783.